Euphemistic Dysphemisms and Their Connection with Obscene Vocabulary in the Youth English Oral Speech of the XXI Century - F.V. Varfolomeev (Язык и текст)
The following article is devoted to the study of euphemistic dysphemisms and their connection with obscene vocabulary in the youth English oral speech of the XXI century. The concepts of "dysphemism" and "euphemistic dysphemism", the peculiarities of their use in oral speech, the connection with profanity are studied. Based on the personal experience and research, some words and expressions of the English language related to euphemistic dysphemisms are presented and contextually analyzed.